How do smart device apps for diabetes self-management correspond with theoretical indicators of empowerment? An analysis of app features - Brew-Sam, Nicola (2020)
Smart device apps for diabetes have the potential to support patients in their daily disease management. However, uncertainty exists regarding their suitability for empowering patients to improve self-management behaviors. This paper addresses a general research gap regarding theoretically based examinations of empowerment in diabetes research, by examining how diabetes app features correspond with conceptual indicators of empowerment.